Pengembangan Kreatifitas Keberbakatan Di Paud Griya Bermain Pangkalpinang Bangka - Makmun, Puri Handayani (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2017)
This research aimed to describe the Creativity development of giftedness in Griya Bermain early childhood education programs Pangkalpinang Bangka. Approach is a qualitative to the type of research description. Data were obtained through intervew, observation, dan documentation and were analyzed using the model. Then tested its validity through persistensice observation and triangulation. The result showed that the the Creativity development of giftedness in Griya Bermain early childhood education programs Pangkalpinang Bangka. Include, (1) Identify creativity of gifted children at school Information obtained from parents, learning process, Information from the child itself, Information from his friend, Not yet the identification